Antioxidant effect of enamel matrix derivative for early phase of periodontal tissue regeneration in diabetes. Issue 8 (28th January 2022) - Takeda, Kohei; Mizutani, Koji; Matsuura, Takanori; Kido, Daisuke; Mikami, Risako; Buranasin, Prima; Saito, Natsumi; Kominato, Hiromi; Takemura, Shu; Nakagawa, Keita; Iwata, Takanori
Abstract: Background: Diabetes involves metabolic disorders in various tissues via hyperglycemia‐induced oxidative stress. This study aimed to investigate the antioxidative effect of enamel matrix derivative (EMD) on periodontal regeneration in diabetes. Methods: Twenty‐two rats were equally divided into streptozotocin (STZ)‐induced diabetes or control group. Two months after induction of hyperglycemia, systemic oxidative stress was measured using urinary 8‐hydroxy‐2′‐deoxyguanosine. EMD or saline was applied into the intrabony defects created in the bilateral maxillary molar. mRNA expressions of inflammatory and oxidative stress markers were quantified (n = 6). Histometric analyses and immunohistochemistry of superoxide dismutase‐1 (SOD‐1) were performed 7 days postoperatively (n = 5). For in vitro experiments, the bone marrow‐derived mesenchymal stem cells were isolated from rat femur and cultured in a high glucose (HG) or control medium. Reactive oxygen species (ROS) measurement and alizarin red staining were performed with/without EMD. Results: Systemic oxidative stress was significantly higher in the diabetic group. The connective tissue attachment and cementum formation were significantly increased at EMD‐treated sites in both diabetic and non‐diabetic groups. The expression of nicotinamide adenine dinucleotide phosphate oxidase two and four was significantly lower at EMD‐treated sites than at EMD‐untreated sites in both diabetic and non‐diabetic rats. Immunohistochemistry showed significantly higher SOD‐1 expression at the EMD‐treated site. In vitro, HG culture had significantly higher ROS production compared with control, which was downregulated by EMD. EMD treatment significantly recovered the impaired calcification in HG. Conclusion: EMD promoted early‐phase wound healing and periodontal tissue regeneration in the surgically created bony defect of STZ‐induced diabetic rat by suppressing hyperglycemia‐induced oxidative stress.